Associations between Self-Reported Daily Affect Ratings and Sleep Duration during the First Two Weeks of Antidepressant Therapy. Issue 1 (2nd January 2021) - Huntley, Edward D.; Swanson, Leslie M.; Kolenic, Giselle E.; Bertram, Holli; Mooney, Ann; Dopp, Richard; Arnedt, J. Todd
ABSTRACT: Background : In the context of a randomized controlled trial evaluating the efficacy of augmenting fluoxetine treatment in young adults with major depressive disorder (MDD) using a modified repeated partial sleep deprivation protocol contrasting 2 weeks of restricted time in bed (i.e., 6 h TIB) to no time in bed restriction (i.e., 8 h TIB) the study examines whether sleep duration and the timing of repeated partial sleep deprivation predicts patient-reported affect ratings. Participants : Participants included 58 young adults with DSM-IV-diagnosed MDD. Methods : Daily ratings of affect and sleep were collected during the first 2 weeks of initiating fluoxetine treatment, yielding 630 person-days. Actigraphy monitoring was employed to assess compliance with time in bed condition. Results : Negative affect ratings and positivity ratios in the morning were more improved among participants assigned to the 6 h TIB condition compared to the 8 h TIB group. Participants whose bedtime was delayed by 2-h nightly demonstrated the most significant improvement in negative affect and positivity ratio during the first 2 weeks of fluoxetine therapy. Moreover, the trajectory of morning negative affect ratings in the first 2 weeks was predictive of remission after 4 weeks of fluoxetine therapy. Conclusions : These findings suggest that monitoring changes in daily affect may be a valuable marker of early treatment response in young adults with MDD.